Drugs for cardiovascular disease in India: perspectives of pharmaceutical executives and government officials on access and development-a qualitative analysis. Issue 1 (December 2016) - Newman, Charles; Ajay, Vamadevan; Srinivas, Ravi; Bhalla, Sandeep; Prabhakaran, Dorairaj; Banerjee, Amitava
Abstract Background India shoulders the greatest global burden of cardiovascular diseases (CVDs), which are the leading cause of mortality worldwide. Drugs are the bedrock of treatment and prevention of CVD. India's pharmaceutical industry is the third largest, by volume, globally, but access to CVD drugs in India is poor. There is a lack of qualitative data from government and pharmaceutical sectors regarding CVD drug development and access in India. Methods By purposive sampling, we recruited either Indian government officials, or pharmaceutical company executives. We conducted a stakeholder analysis via semi-structured, face-to-face interviews in India. Topic guides allow for the exploration of key issues across multiple interviews, along with affording the interviewer the flexibility to examine matters arising from the discussions themselves. After transcription, interviews underwent inductive thematic analysis. Results Ten participants were interviewed (Government Officials:n = 5, and Pharmaceutical Executives:n = 5). Two themes emerged: i) 'Policy-derived Factors'; ii) 'Patient- derived Factors' with three findings. First, both government and pharmaceutical participants felt that the focus of Indian pharma is shifting to more complex, high-quality generics and to new drug development, but production of generic drugs rather than new molecular entities will remain a major activity. Second, current trial regulations in India may restrict India's potential role in the future development of CVD drugs. Third, it is likely that the Indian government will tighten its intellectual property regime in future, with potentially far-reaching implications on CVD drug development and access. Conclusions Our stakeholder analysis provides some support for present patent regulations, whilst suggesting areas for further research in order to inform future policy decisions regarding CVD drug development and availability. Whilst interviewees suggested government policy plays an important role in shaping the industry, a significant force for change was ascribed to patient-derived factors. This suggests a potential role for Indian initiatives that market the unique advantages of its patient population for drug research in influencing national and multinational pharmaceutical companies to undertake CVD drug development in India, rather than simply IP policy-directed factors.